Phenotyping congenital anomalies in England and Scotland: a comparison of three coding clusters using retrospective hospital data. (2017) - Wijlaars, Linda; Zylbersztejn, Ania; Verfürden, Maximiliane; Gilbert, Ruth; Hardelid, Pia
No abstract available